INFECTION PROCESS OF Cercospora coffeicola IN IMMATURE COFFEE FRUITS (Coffee Science - ISSN 1984-3909, 2019)
Cercosporiosis is caused by Cercospora coffeicola and represents very important coffee plants phytosanitary problem. Catuaí IAC 144 and Topázio cultivars at the F2 stage were inoculated with a conidial suspension. Samples were collected at 4, 8, 12, 24, 36, 48, 72, 96, and 168 hours after inoculation (hai) for scanning electron microscope studies. Fungal germination in epidermal surface occurred 4 hai; penetration only through epidermal wounds 12 hai, without appressoria; internal mycelial colonization at 72 hai. The infection in immature coffee fruits implies brown eyespot control management anticipation need, even before the first symptoms.